[(23)sodium MRI for infarct imaging of the human heart] - Sandstede, J; Pabst, T; Beer, M; Harre, K; Bäurle, K; Lipke, C; Butter, F; Kenn, W; Völker, W; Neubauer, S; Hahn, D (2000)
PURPOSE: Sodium is elevated in acute/subacute myocardial infarction due to three distinct mechanisms: Breakdown of ion homeostasis with accumulation of intracellular sodium, extracellular edema formation and, during scar formation, increase of extracellular vs. intracellular space as cardiomyocytes are replaced by connective tissue. 23Na MRI has previously been shown to have the potential to demonstrate myocardial infarction in an animal model. Aim of this study was, therefore, to demonstrate myocardial infarction with the use of 23Na-MRI in patients. MATERIAL AND METHODS: 10 patients were examined 14 +/- 7 days after first myocardial infarction using a 23Na surface coil at 1.5 T. Double angulated short axis images of the entire heart were imaged using an ECG-triggered 3d-FLASH-sequence (FOV, 450 mm; matrix, 64 x 128; spatial resolution, 3.5 x 7 mm2; slice thickness, 16 mm; 32 acquisitions). Areas of elevated sodium signal intensity were correlated with infarct-related wall motion abnormalities imaged by Cine MRI in breathhold-technique. RESULTS: All patients showed an area of elevated sodium signal intensity that correlated well with the clinically determined localization of myocardial infarction as well as with regional wall motion abnormalities detected by Cine MRI. CONCLUSIONS: Elevated 23Na MR image signal intensity demonstrates subacute myocardial infarction in patients.